CHRONIC TENOSYNOVITIS IS ASSOCIATED WITH LOSS OF GRIP STRENGTH IN PATIENTS WITH PSORIASIS AND PSORIATIC ARTHRITIS (OP0069) - Bayat, Sara; Coppers, Birte; Kleyer, Arnd; Godonou, Elie-Tino; Valor, L.; Simon, David; Fagni, Filippo; Corte, Giulia; Schönau, Verena; Tascilar, Koray; Hueber, Axel; Sticherling, Michael; et al. (Annals of the Rheumatic Diseases, 2023)
Background Rheumatic diseases result in joint destruction and impaired physical function [1]. We recently showed, that hand function based on objective tests may serve as a biomarker representing subclinical inflammation in psoriasis (Pso) patients and thus could support the early detection of psoriatic arthritis (PsA) onset [2]. Hand function tests are relevant for objective assessment of musculoskeletal function in relation to disease activity in PsA [3], However, the relationship of hand function with the synovitis and tenosynovitis detected by ultrasound (US) in PsA and Pso patients has not been well studied. Objectives To investigate the association of synovitis and tenosynovitis detected by US in greyscale (GS) and power doppler (PD) activity with grip strength and fine motor skills in patients with PsA and Pso. Methods PsA and Pso patients were recruited from the Rheumatology Department at the University Hospital erlangen, for this cross-sectional study. After giving written informed consent, subject characteristics were recorded and study participants underwent bilateral US of the wrists, metacarpophalangeal (MCP) joints, and flexor tendons of all fingers. Each joint was examined by GS (0-3), PD (0-3) and finally a combined score (PDUS: PD + GS) was calculated (0-3) [4]. The flexor tendon was scanned in GS (0/1) and with PD [0-3]. US activity considered either a synovitis or tenosynovitis score ≥1. Activity in tender joint count (TJC) and swollen joint count (SJC) 68/66 was considered ≥1 tender or ≥1 swollen joint. Hand function was assessed by vigorimetric grip strength (lbf) and the fine motor skill MPUT (Moberg pick-up test). For the analysis, patients’ hands were either divided in dominant/non-dominant or patient reported affected/non-affected hand. A correlation matrix was applied to measure the linear relation between the pairs of synovitis and tenosynovitis scores, grip strength and MPUT for both hands, using the Spearman correlation method. Results 106 patients (40 PsA, 66 Pso) participated in this study. Subject characteristics and general outcomes are summarized in Table 1. While grip strength was higher in the dominant hand (p<0.001), MPUT times are comparable between the dominant vs. non-dominant hands (p=0.056) but was faster in the non-affected hand (p=0.008). Low to moderate positive correlations were observed between both, overall GS synovitis score (MCP 2-5 + wrist) (r=0.24, p<0.05), and PDUS (r=0.23, p<0.05) with MPUT. In US active patients, a high correlation between grip strength and GS tenosynovitis score in digit 2 (r=-0.566, p=0.028) was detected. When considering patients with US in addition to SJC/TJC activity, imaging modalities did not correlate with hand function. Conclusion These findings indicate that the synovitis detected by greyscale is related with fine motor skills and tenosynovitis in greyscale with grip strength. This suggests, that chronic tenosynovitis has a greater impact on hand function than the acute inflammatory phase. When considering patients with TJC68/SJC66 ≥1 this relation is not present, suggesting that clinically assessed joint count, unlike ultrasonography, does not correlate with hand function impairmen